2008
DOI: 10.1269/jrr.07077
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Reduces Oxidative Stress Induced by Chronic Exposure of Microwave Radiation from Mobile Phones in Rat Brain

Abstract: We demonstrated two important findings; that mobile phones caused oxidative damage biochemically by increasing the levels of MDA, carbonyl groups, XO activity and decreasing CAT activity; and that treatment with the melatonin significantly prevented oxidative damage in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 40 publications
6
79
2
2
Order By: Relevance
“…XO has previously been reported to be increased in brain tissue after seven days of exposure to a 900 MHz electromagnetic field [5]. In an earlier publication, the current authors also reported an XO increase in brain tissue after 40 and 60 days of exposure to MWs [7]. As far as the authors are aware, changes in XO activity in testicular tissue exposed to MWs have not previously been reported.…”
Section: Microwaves and Oxidative Stress In Testicular Tissuementioning
confidence: 51%
See 1 more Smart Citation
“…XO has previously been reported to be increased in brain tissue after seven days of exposure to a 900 MHz electromagnetic field [5]. In an earlier publication, the current authors also reported an XO increase in brain tissue after 40 and 60 days of exposure to MWs [7]. As far as the authors are aware, changes in XO activity in testicular tissue exposed to MWs have not previously been reported.…”
Section: Microwaves and Oxidative Stress In Testicular Tissuementioning
confidence: 51%
“…Malondialdehyde (MDA) increases and changes in catalase activity in testes, kidneys and skin have previously been reported after exposure to MWs [4][5][6]. Xanthine oxidase (XO), an enzyme able to produce reactive oxygen species (ROS), is reported to be elevated in the brain tissue after exposure to MWs [5,7]. Secondary products of lipid peroxidation, particularly MDA, have large-scale cytotoxic effects.…”
mentioning
confidence: 99%
“…The exposure condition in our study, or what is called whole-body exposure system, was similarly used by other researchers who did not apply the MPs directly to the animal heads. 22 We did not apply this head-only exposure in this study as this model has obviously some intrinsic limitations. First, owing to the much smaller body size of the rabbit, the ratio of the head to the whole-body specific absorption rate is very different in rabbits compared with humans.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these obvious differences in the exposure protocol, a negative effect of MPs was shown in our current study and that of the researchers who applied a quite similar protocol. 22 A large body of evidence has implicated the testosterone and dopamine in the control of male sexual behavior in rabbits and other vertebrate species. 23,24 Testosterone has a key role in initiating and maintaining the sexual behavior in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation